2008
DOI: 10.1080/15459620802558196
|View full text |Cite
|
Sign up to set email alerts
|

N95 and P100 Respirator Filter Efficiency Under High Constant and Cyclic Flow

Abstract: This study investigated the effect of high flow conditions on aerosol penetration and the relationship between penetration at constant and cyclic flow conditions. National Institute for Occupational Safety and Health (NIOSH)-approved N95 and P100 filtering facepiece respirators and cartridges were challenged with inert solid and oil aerosols. A combination of monodisperse aerosol and size-specific aerosol measurement equipment allowed count-based penetration measurement of particles with nominal diameters rang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
71
1
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(88 citation statements)
references
References 14 publications
11
71
1
5
Order By: Relevance
“…For both respirators in their original condition, the MPPS using NaCl test aerosol was around 40 nm, which is similar to the 40 to100 nm range reported by other investigators for similar respirator filters and experimental conditions (Martin and Moyer, 2000;Balazy et al, 2006;Huang et al, 2007, Eshbaugh et al, 2009Renagasamy et al, 2009). After treatment with isopropanol, the MPPS for both respirators increased to 154 nm.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…For both respirators in their original condition, the MPPS using NaCl test aerosol was around 40 nm, which is similar to the 40 to100 nm range reported by other investigators for similar respirator filters and experimental conditions (Martin and Moyer, 2000;Balazy et al, 2006;Huang et al, 2007, Eshbaugh et al, 2009Renagasamy et al, 2009). After treatment with isopropanol, the MPPS for both respirators increased to 154 nm.…”
Section: Discussionsupporting
confidence: 86%
“…The 30 L min -1 was selected to represent low to moderate workload; 85 L min -1 is used for NIOSH respirator filter certification tests and represents a moderate to high workload; 130 L min -1 represents inhalation at a very heavy workload. It is also represents the peak inspiratory flow of a cyclic flow with a mean inspiratory flow of 85 L min -1 (Eshbaugh et al, 2009). Aerosol concentrations were measured with a scanning mobility particle sizer (SMPS, GRIMM Aerosol Technologies, Douglasville, GA).…”
Section: Test Chambermentioning
confidence: 99%
“…2, increasing flow rate resulted in decreased absolute protection efficiencies (E AP ) for all N95 types tested (ANOVA tests; p-value: 0.050 for N95-9010, 0.000 for N95-9031 and 0.041 for N95-9042) and other FFRs (all p-values o0.05). Other studies also found penetration of submicron aerosols increased under high cyclic and constant flow conditions (Eshbaugh et al, 2008;Hofacre et al, 2006).…”
Section: Protective Performance Of Commercially Available Masksmentioning
confidence: 83%
“…The existence of the leak may be the main reason, and large particles penetrated into the manikin not from the respirators, but from the leak. Numerous studies have shown that the most penetrating particles for N95 respirators are submicron particles (Weber et al, 1993;Eshbaugh et al, 2008). Unfortunately, the lower detection limit of UV-APS is 0.37 mm and it fails to offer detailed information for particles smaller than 0.37 μm including single viruses.…”
Section: Protective Performance Of Commercially Available Masksmentioning
confidence: 99%
“…An increase in flow rate corresponded to an increase in filter penetration in various studies (Eshbaugh et al 2009;Eninger et al 2008;Balazy et al 2006), hence penetration reported in the Janssen and Penconek studies would potentially be lower than penetration measured if the study was conducted at the standard specified flow rates.…”
Section: Introductionmentioning
confidence: 96%